IDENTITAS MASKULIN PADA DESAIN INTERIOR TOKO-RETAIL BUSANA PRIA: STUDI KASUS TOKO-RETAIL BUSANA PRIA DI PUSAT PERBELANJAAN JAKARTA - Nani Sriwardani (ATRAT: Jurnal Seni Rupa, 2013)
In this discussion, looked upon the visual interior context such as in the retail clothing stores at the center malls. At this research, male identity is used as the background and the indicator to seek appropriateness over position and application of any interior design around clothing stores. Several observations had also been done to analyze any applied visual interior in stores specifically the object studied clothing stores. Some of the studied objects were these clothing stores such as Harley Davidson (PIM2) and Nautica (PS) were targeted for males. All those two designated and studied stores were supposed to represent various classifications of clothing stores that are available at shopping centers. The result of the field observation showed that the two stores had some visual similarities and differences.Keywords: Male Identity, Male Dress, Retail Shop Interior